Absence Epilepsy Psychosocial Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The long-term psychosocial outcome in 56 patients aged 18 years or older with typical absence epilepsy and 61 controls with juvenile rheumatoid arthritis (JRA) was studied at the Royal University Hospital, Saskatoon, Saskatchewan, and the Izaak Walton Killam-Grace Health Center, and Dalhousie University Faculty of Medicine, Halifax, Nova Scotia, Canada.